E-COMMERCE BUSINESS DIGITAL TRANSFORMATION - Dirgantara Bayu Aji Pamungkas; Jodi Setiyawan; Fandi Gunawan; Asep Muhamad Taufik; Muhammad Rasyiid Nandiwardhana; Bob Hardian Syahbuddin (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Digital ecosystem has rapidly grown in Indonesia. E-commerce has become the most disruptive among others. XYZ is one of the Indonesian e-commerce platforms. They choose to keep evolving through digital transformation to align with the current need. This research aims to identify XYZ's digital transformation to meet current business, partners, and customers' needs. Data were obtained by interviewing and collecting company documents, and Gupta's framework was chosen for analysis. The transformations which have been done by XYZ are changing the strategy market-based view into a resource-based view. XYZ also transformed from e-commerce to a business segment platform with a B2B2B model. The Gupta framework is used as the foundation for this transformation. The results of the Gupta framework are translated into strategies for achieving new company structure and values